Electronic, vibrational, and charge-transport properties of benzothienobenzothiophene–TCNQ co-crystals. (12th August 2020) - Ashokan, Ajith; Hanson, Caitlin; Corbin, Nathan; Brédas, Jean-Luc; Coropceanu, Veaceslav
Abstract : The electronic, optical, vibrational, and charge-transport properties of a series of benzothienobenzothiophene–TCNQ co-crystals are discussed on the basis of density functional theory calculations. Abstract : The electronic, vibrational, and charge-transport properties of a series of benzothieno-benzothiophene (BTBT)–F m TCNQ ( m = 0, 2, 4) and diC n BTBT–F m TCNQ ( n = 8, 12; m = 0, 4) donor–acceptor (DA) co-crystals have been investigated by means of density functional theory calculations. The electronic-structure calculations predict wide conduction bands and small effective masses for electrons along the DA stacking directions. The results indicate that the increase in the number of F atoms on the acceptor molecules results in an increase of superexchange couplings along the DA stacks, while the addition of the alkyl side chains results in a decrease of through-space transfer integrals between neighboring stacks. Time-dependent density functional theory calculations of the optical properties describe the lowest two optical transitions as having a charge-transfer character and being related to the two electronic coupling pathways that contribute to the superexchange couplings. The results also indicate that the ionicity parameter in the diC n BTBT–F m TCNQ cocrystals is somewhat larger than in the BTBT analogues. Overall, we find that DFT calculations based on periodic boundary conditions are a reliable tool to estimate the ionicity parameter in DA cocrystals.